1990
DOI: 10.1148/radiology.175.1.2315480
|View full text |Cite
|
Sign up to set email alerts
|

Dural arteriovenous fistulas: evaluation with MR imaging.

Abstract: The preangiographic diagnosis of cerebral dural arteriovenous fistula (DAVF) can be difficult. The magnetic resonance (MR) images of 12 patients with angiographically proved DAVF were evaluated to characterize the appearance of these lesions and to identify those patients at increased risk for complications. Patients with DAVF demonstrating venous occlusive disease are at higher risk for complications from the arterialized collateral venous system. This venous occlusive disease is demonstrated best at arteriog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(36 citation statements)
references
References 0 publications
2
34
0
Order By: Relevance
“…21,28,29 Studies have used a variety of techniques and sequences and have shown variable diagnostic performance. De Marco et al 28 presented some of the earliest data, finding MR imaging cortical vein dilation and venous occlusion in 8 of 12 patients with angiographically proved DAVF by using basic spin-and gradient-echo sequences. This description is contrary to the present experience in which the presence of cortical venous dilation was relatively rare, 2/7.…”
Section: Discussionmentioning
confidence: 99%
“…21,28,29 Studies have used a variety of techniques and sequences and have shown variable diagnostic performance. De Marco et al 28 presented some of the earliest data, finding MR imaging cortical vein dilation and venous occlusion in 8 of 12 patients with angiographically proved DAVF by using basic spin-and gradient-echo sequences. This description is contrary to the present experience in which the presence of cortical venous dilation was relatively rare, 2/7.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional MR imaging, however, often shows prominent flow voids on the surface of the brain in patients with DAVFs with RCVD. [9][10][11][12] Highintensity lesions in the deep white matter revealed by T2-weighted imaging are secondary to the venous hypertension and venous congestion. The combination of prominent flow voids on the surface of the brain and high intensity lesions in T2-weighted images within the deep white matter is highly suggestive of a DAVF.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Several investigators have previously reported that MR-DSA is a reliable technique for the screening and monitoring of DAVFs, despite its temporal-and spatialresolution limitations, and that it clearly shows RCVD. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] MR-DSA provides reliable information that can be used to determine the need for patients with DAVFs to undergo additional angiography. 16 A recent study reported that the increased cerebral blood volume in the affected hemisphere of patients with DAVFs with RCVD could be demonstrated with DSC because RCVD causes an increase in cerebral blood volume as a result of the dilation of cerebral veins.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] However, the clinical use of these techniques remains limited because of the lack of hemodynamic information and the possibility of misdiagnosis. [7][8][9][10][11][12] Time-resolved contrast-enhanced MR angiography (MRA) at 1.5T has been applied to the diagnosis of intracranial DAVF.…”
mentioning
confidence: 99%